1975
DOI: 10.1111/j.1751-1097.1975.tb06698.x
|View full text |Cite
|
Sign up to set email alerts
|

The Photolability of Dna Containing 5‐bromouracil‐i. Single‐strand Breaks and Alkali‐labile Bonds*

Abstract: The proportions of single-strand breaks and alkali-labile bonds produced by UV-light were investigated in covalently-closed circular 5-bromouracil (BrUra)-containing I-phage DNA. When BrUra--DNA was irradiated in 0.01 M Tris-0.001 M EDTA (pH 8.1) buffer, the Do was 11.7 J/m2 for single-strand breaks, 2.25 J/mz for total breaks, and 2.8 J/m2 for alkali-labile bonds. Thus. alkalilabile bonds were the predominant photochemical products. No double-strand breaks were observed aftcr exposure to 7.7 times the Do for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The lower buoyant density of the substituted mtDNA strands encountered in most experiments might be due to the presence of a region of neighboring BU bases which were preferentially degraded during alkali denaturation as the result of BU-induced single-strand breaks. Moreover, these observations, as well as those of others (15,23), suggest that BrdUMP substitution in DNA increases its lability to alkaline treatment. It could also be argued that the density of 1.703 g/ml represents an intermediate density between the light and heavy strands due to recombinational events.…”
Section: Resultssupporting
confidence: 73%
“…The lower buoyant density of the substituted mtDNA strands encountered in most experiments might be due to the presence of a region of neighboring BU bases which were preferentially degraded during alkali denaturation as the result of BU-induced single-strand breaks. Moreover, these observations, as well as those of others (15,23), suggest that BrdUMP substitution in DNA increases its lability to alkaline treatment. It could also be argued that the density of 1.703 g/ml represents an intermediate density between the light and heavy strands due to recombinational events.…”
Section: Resultssupporting
confidence: 73%
“…Halogen-substituted pyrimidines have been investigated since the 1960s owing to their potential application in the phototherapy of cancer diseases: it was demonstrated that halogenouracils, notably 5-bromouracil ( Br U), when incorporated in DNA, sensitize it to UV radiation. Indeed, exposure of DNA containing 5-bromouridine to radiation of 250−320 nm produces several types of DNA damage such as direct strand breaks, alkali-labile sites, and intra- and interstrand photo-cross-links. These effects are attributed to a highly reactive vinyl uracil-5-yl radical, produced from Br U by UV quanta. , The damaging action of the uracil-5-yl radical seems to be related to its ability to abstract hydrogen atoms from the sugar constituents of DNA.…”
Section: Introductionmentioning
confidence: 99%